The metabolism of L-arginine and its significance for the biosynthesis of endothelium-derived relaxing factor: cultured endothelial cells recycle L-citrulline to L-arginine. - Hecker, M (1990)
We have investigated the mechanism by which cultured endothelial cells generate L-arginine (L-Arg), the substrate for the biosynthesis of endothelium-derived relaxing factor. When Arg-depleted endothelial cells were incubated in Krebs' solution for 60 min, L-Arg levels were significantly (9.7-fold) elevated. The generation of L-Arg coincided with a substantial decrease (90%) in intracellular L-glutamine (L-Gln), whereas all other amino acids were virtually unaffected. Changes in calcium, pH, or oxygen tension had no effect on L-Arg generation, which was, however, prevented when the cells were incubated in culture medium containing L-Gln. L-Arg generated by endothelial cells labeled with L-[14C]Arg was derived from an unlabeled intracellular source, for the specific activity of the intracellular L-Arg pool decreased substantially (8.8-fold) over 60 min. Arg-depleted endothelial cells did not form urea or metabolize L-ornithine but converted L-citrulline (L-Cit) to L-Arg possibly via formation of L-argininosuccinic acid. Nondepleted cells stimulated with the calcium ionophore A23187 showed only a transient accumulation of L-Cit, indicating that L-Cit is recycled to L-Arg during the biosynthesis of endothelium-derived relaxing factor. The generation of L-Arg by Arg-depleted endothelial cells was partially (45%) blocked by protease inhibitors, and various Arg-containing dipeptides were rapidly cleaved to yield L-Arg. Thus, cultured endothelial cells recycle L-Cit to L-Arg and possibly liberate peptidyl L-Arg. The Arg-Cit cycle appears to be the equivalent in the endothelial cell to the formation of urea by the liver. The biosynthesis of endothelium-derived relaxing factor may, therefore, not only produce a powerful vasodilator but also relieve the endothelial cell of excess nitrogen.